If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(F)=5F^2-2F+1/2
We move all terms to the left:
(F)-(5F^2-2F+1/2)=0
We get rid of parentheses
-5F^2+F+2F-1/2=0
We multiply all the terms by the denominator
-5F^2*2+F*2+2F*2-1=0
Wy multiply elements
-10F^2+2F+4F-1=0
We add all the numbers together, and all the variables
-10F^2+6F-1=0
a = -10; b = 6; c = -1;
Δ = b2-4ac
Δ = 62-4·(-10)·(-1)
Δ = -4
Delta is less than zero, so there is no solution for the equation
| 26+3y=5y | | 9÷2r=14 | | 78=-2(m+3)=m | | 5x(5+3x)=17 | | x/2+x/3=(x+7)/3 | | (1/4)b-5=3 | | 6f÷7=49 | | 4+f=f | | 3(4^x/2)=96 | | 2/x+5/2x=9 | | 3+7x=60 | | 14/12x+22/10x=x | | (y+10+3y-2)=180 | | 3x+3=67+12 | | 4h÷1=21 | | (x+7)2-49=0 | | 16x+31-13x+11=82 | | 70-7b=9b | | 10u=100,000 | | (250+x)+x=1000 | | 12-2a=7a-15 | | 9^x=47 | | u=24/5 | | X^2+17x+25=0 | | 17+3y=50 | | 2f–5=1 | | 6Xc=53+8+12 | | 192=-8p+8(6p-6) | | (6n+5)/(2n^2=3n) | | 3x+3x=16+8x | | 5z-1=3 | | 7+7x=13+9x |